Enhancing the impact of online simulations through blended learning: A critical incident approach. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to describe an approach for utilising a critical incident method within the context of an online business simulation game in order to provide an effective framework for reflective learning.Design/methodology/approach – The paper presents a review of pertinent literature to place the critical incident technique within the novel context of simulation gaming. Through presenting a case study of practice, it goes on to describe a blended learning approach that combines online simulation with post‐simulation reflection based on the critical incident method. An action research approach is adopted as a framework for reflection on practice.Findings – From a conceptual perspective, there are a number of potential benefits to employing a critical incident approach combined with simulation gaming. The ability of educators to compress time frames and manage the introduction of critical incidents allows students to learn in a way that would not be possible in the real world. Furthermore, carefully designed post‐simulation debriefing, structured around a critical incident framework, has the potential to enhance the learning impact of online simulation.Research limitations/implications – The research is limited in that a single case study context is described. Further evaluation research is required to fully assess the benefits of the approach adopted.Originality/value – The study explores the use of the critical incident approach within the novel context of online simulation gaming. It provides educators with a blended learning method that can be employed to enhance the impact of e‐learning through structured reflection.